68Ga-FAPI-04 PET/CT in Epithelioid Hemangioendothelioma With Pleura and Bone Metastases. (27th October 2022) - Chen, Jie; Li, Chongjiao; Tian, Yueli; Wen, Bing; He, Yong
Abstract: Epithelioid hemangioendothelioma is a low- to intermediate-grade malignant vascular tumor with a slowly progressive course and unpredictable prognosis. We report a case of epithelioid hemangioendothelioma with pleura and bone metastases on 68 Ga-FAPI-04 PET/CT in a 65-year-old woman who underwent surgery and chemotherapy.